Analisis Dan Perancangan Sistem Informasi Pelayanan Administrasi Desa Berbasis Web Pada Desa Lolowonu Niko'otano - Fajar Laskar Harefa; Agus Fortiman Telaumbanua; Cerahman Halawa; Jurisman Waruwu (CV. SINAR HOWUHOWU, 2026)
The development of information technology has pushed for digitalization in public services, including village administrations. Lolowonu Niko'otano Village still relies on conventional methods for managing citizen data, archiving documents, and issuing letters, resulting in delays and data loss risks. This study aims to analyze, design, and implement a Web-Based Village Administration Information System using the Waterfall development model. System features focus on population data management, administrative letter requests, and automated reporting. System functionality was evaluated using Black Box Testing, while usability was measured using the System Usability Scale (SUS). The Black Box results confirmed that all features functioned correctly according to user requirements. The SUS evaluation showed high user acceptance, indicating that the system effectively improves the speed, accuracy, and overall quality of public services in the village.